STRATEGI GURU DALAM PEMBENTUKAN AKHLAK SISWA MELALUI HABITUASI ISLAMI DI MTS TPI GUNUNG MELAYU KAB. ASAHAN - Maratu Naja Ramadhan; Dedi Masri; Zulham Zulham (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2025)
This study aims to determine the strategies employed by Akidah Akhlak (Islamic Beliefs and Morals) teachers in shaping students' morals (akhlak) through Islamic habituation at MTs TPI Gunung Melayu, Asahan Regency. This research is motivated by a decline in student morals, such as a lack of courtesy toward teachers, the use of inappropriate language, and the negative influences of both the environment and technology. This study utilized a qualitative approach with field research. The research subjects were the Akidah Akhlak teacher and the headmaster, while the research object consisted of class VIII-II students. Data were collected through observation, interviews, and documentation, and subsequently analyzed using data reduction, data display, and conclusion drawing through triangulation. The results indicate that Islamic habituation encompasses practicing Islamic greetings (salam), prayer (doa), congregational prayers (shalat berjamaah), reading the Qur'an, and polite behavior. The teacher's strategies are implemented through role modeling, habituation, advice, supervision, and educational sanctions. Consequently, the strategy of the Akidah Akhlak teacher through Islamic habituation plays a vital role in shaping students' morals.